2019
DOI: 10.1016/j.surfcoat.2019.06.073
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion and tribocorrosion behaviour of titanium nitride thin films grown on titanium under different deposition times

Abstract: Ti and its alloys exhibit combination of unique properties for biomedical applications, however their poor triboelectrochemical behaviour is a major concern. Therefore, TiN coatings were deposited on cp-Ti (grade 4) by sputtering technique aiming the improvement of its tribocorrosion behaviour. The properties of the coated samples, using different TiN deposition times, were characterized by using grazing incidence X-ray diffraction, FIB-SEM, and nanoindentation. The corrosion behaviour was studied by electroch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(17 citation statements)
references
References 68 publications
0
17
0
Order By: Relevance
“…The Daimler-Benz Rockwell C adhesion test is a fast and easy method that has been studied to evaluate the adhesion of hard coatings [44,53,54] that can also be used for TNT layers [55]. The Daimler-Benz Rockwell-C adhesion test results are shown in Fig.…”
Section: Adhesion Behavior Of Nanotubular Filmsmentioning
confidence: 99%
“…The Daimler-Benz Rockwell C adhesion test is a fast and easy method that has been studied to evaluate the adhesion of hard coatings [44,53,54] that can also be used for TNT layers [55]. The Daimler-Benz Rockwell-C adhesion test results are shown in Fig.…”
Section: Adhesion Behavior Of Nanotubular Filmsmentioning
confidence: 99%
“…Because of having a golden color, the TiN films are used as decorative coatings. [94] TiN thin films have their applications in different fields such as automobiles, [92] machining tools, [96] solar cells, [96] biomedical, [97][98][99] electroanalytical applications, [100] supercapacitors, [101,102] micro electromechanical systems (MEMS) devices, [86,103] aerospace, electronics, [104,105] etc.…”
Section: Applications Of Tin Thin Filmsmentioning
confidence: 99%
“…Furthermore, previous studies found TiN coatings nontoxic, biocompatible and bioactive with the ability to reduce the release of toxic metallic ions from Ti-6Al-4V alloy [11,[21][22][23]. Caha et al [24] reported that TiN coating improves corrosion and tribocorrosion performance of pure titanium substrate.…”
Section: Introductionmentioning
confidence: 99%